2021
DOI: 10.1200/jco.2021.39.6_suppl.41
|View full text |Cite
|
Sign up to set email alerts
|

The role of androgen deprivation therapy on the clinical course of COVID-19 infection in men with prostate cancer.

Abstract: 41 Background: TMPRSS2, a cell surface protease which is commonly upregulated in prostate cancer (PC) and regulated by androgens, is a necessary component for SARS-CoV2 cellular entry into respiratory epithelial cells. PC patients receiving ADT were reported to have a lower risk of SARS-CoV-2 infection. However, whether ADT may have an impact on the severity of COVID-19 illness in this population is poorly understood. Methods: In this study performed across 7 US medical centers, we retrospectively evaluated p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Patients undergoing ADT have been reported to express lower levels of TMPRSS2, and may be less affected by COVID-19 [103]. Montopoli and colleagues reported an association between ADT and reduced occurrence of SARS-CoV-2 infection, whereas others found no beneficial effect of ADT on SARS-CoV-2 infection or COVID-19 progression [177][178][179][180][181][182]. However, the fact that the study cohorts consisted of men suffering from prostate cancer limits the applicability of the results to non-cancer patients with COVID-19.…”
Section: Clinical Evaluation Of Tmprss2 Inhibitors In Covid-19 Patientsmentioning
confidence: 99%
“…Patients undergoing ADT have been reported to express lower levels of TMPRSS2, and may be less affected by COVID-19 [103]. Montopoli and colleagues reported an association between ADT and reduced occurrence of SARS-CoV-2 infection, whereas others found no beneficial effect of ADT on SARS-CoV-2 infection or COVID-19 progression [177][178][179][180][181][182]. However, the fact that the study cohorts consisted of men suffering from prostate cancer limits the applicability of the results to non-cancer patients with COVID-19.…”
Section: Clinical Evaluation Of Tmprss2 Inhibitors In Covid-19 Patientsmentioning
confidence: 99%
“…1. After applying the inclusion and exclusion criteria six studies (Patel et al updated their study in 2021 [18,21]) were included for systematic review; Caffo et al was excluded from the meta-analysis due to the lack of a control group [22].…”
Section: Selection Processmentioning
confidence: 99%
“…Table 2 illustrates the characteristics of the five included studies. Four and five studies reported the risk of SARS-CoV-2 infection and severe COVID-19, respectively [16][17][18][19][20][21]. The reported outcomes including the odds ratio or hazard ratio of the SARS-CoV-2 infection and severe disease risks from the included studies are mentioned in Table 3.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…A search of the PubMed and Scopus databases and the proceedings of ASCO, ESMO, AUA, and EAU meetings from 1 January 2020 to 1 September 2021 identified 14 studies reporting the outcomes of PC patients with SARS-CoV-2 infection: five were published in the form of full papers (Caffo et al, 2020a;Di Lorenzo et al, 2020;Jimenez-Alcaide et al, 2021;Klein et al, 2021;Montopoli et al, 2020), and the others as letters (5) (Caffo et al, 2020b;Dalla Volta et al, 2020;Koskinen et al, 2020;Kwon et al, 2021;Patel et al, 2020) or meeting abstracts (4) (Duarte et al, 2021;Patel et al, 2021;Sbrana et al, 2020;Tucker et al, 2021). The results are summarised in Table 1.…”
Section: Clinical Outcomes Of Sars-cov-2 Infection In Pc Patients Rec...mentioning
confidence: 99%
“…Two studies investigated infection severity in terms of mortality and intensive care unit (ICU) admissions and, in these cases, severe outcomes were recorded in respectively 16.6 % and 25 % of patients (Koskinen et al, 2020;Montopoli et al, 2020). Comparison of infection severity by ADT use did not reveal any statistically significant difference in mortality in most cases (Jimenez-Alcaide et al, 2021;Koskinen et al, 2020;Kwon et al, 2021;Montopoli et al, 2020;Patel et al, 2020Patel et al, , 2021; the only one that suggested ADT had a statistically significant favourable impact on mortality only evaluated the outcomes of hospitalised patients (Duarte et al, 2021).…”
Section: Clinical Outcomes Of Sars-cov-2 Infection In Pc Patients Rec...mentioning
confidence: 99%